Concurrent Validity of Functional Gait Assessment, Timed Up and Go, and Gait Speed Tests in the Persian Community-Dwelling Elderly - Ahmad Ali Akbari Kamrani; Seyed Hojjat Zamani Sani; Zahra Fathi Rezaie; Mohammad Taghi Aghdasi (Iranian Rehabilitation Journal, 2010)
Objectives: The purpose of this study was to evaluate the concurrent validity of the Farsi version of Functional Gait Assessment (FGA), Timed Up & Go (TUG), and Gait Speed tests in Persian communitydwelling older adults.